2018
DOI: 10.1007/s10100-018-0580-5
|View full text |Cite
|
Sign up to set email alerts
|

Interval linear programming under transformations: optimal solutions and optimal value range

Abstract: Interval linear programming provides a tool for solving real-world optimization problems under interval-valued uncertainty. Instead of approximating or estimating crisp input data, the coefficients of an interval program may perturb independently within the given lower and upper bounds. However, contrarily to classical linear programming, an interval program cannot always be converted into a desired form without affecting its properties, due to the so-called dependency problem.In this paper, we discuss the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…In Garajová et al [10], it was also observed that the first transformation may change finite optimal values in the case with interval A. Below, we show by an example that this is also true for the second transformation.…”
Section: Special Cases With a Realsupporting
confidence: 64%
See 3 more Smart Citations
“…In Garajová et al [10], it was also observed that the first transformation may change finite optimal values in the case with interval A. Below, we show by an example that this is also true for the second transformation.…”
Section: Special Cases With a Realsupporting
confidence: 64%
“…Nevertheless, in some cases, it is possible. Garajová et al [10] showed that provided A is real, finite optimal values (and therefore also f fin ) is not changed under the following transformations:…”
Section: Special Cases With a Realmentioning
confidence: 99%
See 2 more Smart Citations
“…Linear programming is a classical approach in OR that provides new research challenges until today. The paper written by Garajová et al (2018) considers the interval linear programming that is a tool when the optimization problems are to be solved under interval-valued uncertainty. Tavakoli and Klavžar (2019) address a discrete optimization problem studying global defensive k-alliances.…”
mentioning
confidence: 99%